A newly identified emission-line region around P Cygni. Issue 1 (18th August 2018) - Mizumoto, Misaki; Kobayashi, Naoto; Hamano, Satoshi; Ikeda, Yuji; Kondo, Sohei; Sameshima, Hiroaki; Matsunaga, Noriyuki; Fukue, Kei; Yasui, Chikako; Izumi, Natsuko; Kawakita, Hideyo; Nakanishi, Kenshi; et al.
ABSTRACT: We present a high-resolution ( R  ≃ 20  000) near-infrared (9100–13 500Å) long-slit spectrum of P Cygni obtained with the newly commissioned WINERED spectrograph in Japan. In the obtained spectrum, we have found that the velocity profiles of the [Fe ii ] emission lines are resolved into two peaks at a velocity of ≃220 km s −1 with a moderate dip in between and with additional sub-peaks at ≃±100 km s −1 . The sub-peak component is confirmed with the long-slit echellogram to originate in the known shell with a radius of ≃10 arcsec, which was originally created by the outburst in 1600 ad . On the other hand, the ≃220 km s −1 component, which dominates the [Fe ii ] flux from P Cygni, is found to be concentrated closer to the central star with an apparent spatial extent of ≃3 arcsec. The extent is much larger than the compact (<0.1 arcsec) regions traced with hydrogen, helium, and metal permitted lines. The velocity, estimated mass, and dynamical time of the extended emission-line region suggest that the region is an outer part of the stellar wind region. We suggest that the newly identified emission-line region may trace a reverse shock due to the stellar wind overtaking the outburst shell.